Enhancing the Thermal Stability and Combustion Performance of NC-Based Propellants via Bu-NENA Modification - Yuan, Zhifeng (Langmuir : the ACS journal of surfaces and colloids, 2024)
In this paper, a series of insensitive smokeless nitrocellulose (NC)-based propellants were prepared through the absorption rolling method. Their thermal stability was rigorously assessed via vacuum stability test (VST), and their thermal reactivity of the propellant was comprehensively investigated and compared using the thermogravimetric analysis (TG)/differential scanning calorimetry (DSC) technique. Additionally, the combustion characteristics were meticulously analyzed by a constant-volume combustion diagnosis system. The experimental results showed that the thermal stability of the propellant was significantly enhanced when N-butyl-N-nitratoethyl nitramine (Bu-NENA) was used to partially or fully replace nitroglycerin (NG). However, an increase in Bu-NENA content corresponded with a decrease in the burning rate of the propellant. The catalytic effects observed in propellants varied markedly, influencing the composition of the products formed during thermal decomposition. Specifically, substituting 50 and 100% of NG with Bu-NENA resulted in reductions in the decomposition heat release of 96.2 and 258 J·g-1, respectively. Furthermore, the introduction of the catalyst significantly increased the burning rate under low-pressure conditions. For instance, at 2 MPa, the burning rate of Bu-0503 increased from 1.78 to 5.23 mm·s-1. A lower content of Bu-NENA was associated with a more luminous flame, while substituting 50 and 100% of NG with Bu-NENA led to decreases in flame temperature by 222 and 535 °C, respectively. The observed decrease in the flame temperature is attributed to the heat absorption during the volatilization of Bu-NENA, leading to a reduction in the thermal feedback of the flame